2009
DOI: 10.2141/jpsa.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Frequency in Asian Native Chicken Populations and Gene Expression Using Insulin-like Growth Factor 1 (IGF1) Gene Promoter Polymorphism

Abstract: A single nucleotide polymorphism (SNP) site, alleles and within promoter region of gene ( ) showed significant association with chicken growth, body composition and skeletal traits. In the present study, we performed genotyping of this SNP in Asian native chicken populations, layer and broiler populations using PCR-RFLP and comparison of gene expression level and growth traits among the SNP genotypes. By the PCR-RFLP, allele frequency was estimated to be within the range of .. in Asian native chicken populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…The CC homozygous genotype was not found at all in the broiler population. This confirms a study by Moe et al (2009) in which also no CC genotype was found in Cobb broilers.…”
Section: Average Values Of Phenotypic Traits and Associations Of The supporting
confidence: 91%
See 4 more Smart Citations
“…The CC homozygous genotype was not found at all in the broiler population. This confirms a study by Moe et al (2009) in which also no CC genotype was found in Cobb broilers.…”
Section: Average Values Of Phenotypic Traits and Associations Of The supporting
confidence: 91%
“…In this study, we investigated the genotypic and allelic frequencies of SNP within the chicken IGF1 gene promoter region in two broiler populations. The allele frequencies of IGF1-SNP1 were in Hardy-Weinberg equilibrium, suggesting that the IGF1 polymorphism does not affect the fitness of birds (Moe et al 2009). In both commercial broiler lines, the allelic frequency of A was higher than that of the allele C. This result suggests that the broilers as chickens bred for high intensity growth, were high in distribution of allele A.…”
Section: Average Values Of Phenotypic Traits and Associations Of The mentioning
confidence: 86%
See 3 more Smart Citations